Salinity has little effect on photosynthetic and respiratory responses to seasonal temperature changes in black mangrove (Avicennia germinans) seedlings. (17th August 2020) - Aspinwall, Michael J; Faciane, Martina; Harris, Kylie; O'Toole, Madison; Neece, Amy; Jerome, Vrinda; Colón, Mateo; Chieppa, Jeff; Feller, Ilka C
Abstract: Temperature and salinity are important regulators of mangrove range limits and productivity, but the physiological responses of mangroves to the interactive effects of temperature and salinity remain uncertain. We tested the hypothesis that salinity alters photosynthetic responses to seasonal changes in temperature and vapor pressure deficit ( D ), as well as thermal acclimation _of leaf respiration in black mangrove ( Avicennia germinans ). To test this hypothesis, we grew seedlings of A. germinans in an outdoor experiment for ~ 12 months under four treatments spanning 0 to 55 ppt porewater salinity. We repeatedly measured seedling growth and in situ rates of leaf net photosynthesis ( A sat ) and stomatal conductance to water vapor ( g s ) at prevailing leaf temperatures, along with estimated rates of Rubisco carboxylation ( V cmax ) and electron transport for RuBP regeneration ( J max ), and measured rates of leaf respiration at 25 °C ( R area 25 ). We developed empirical models describing the seasonal response of leaf gas exchange and photosynthetic capacity to leaf temperature and D, and the response of R area 25 to changes in mean daily air temperature. We tested the effect of salinity on model parameters. Over time, salinity had weak or inconsistent effects on A sat, g s and R area 25 . Salinity also had little effect on the biochemical parameters of photosynthesis ( V cmax, J max ) and individual measurements of A sat, g s, V cmax and J max showed a similar response to seasonal changes in temperature and D across all salinity treatments. Individual measurements of R area 25 showed a similar inverse relationship with mean daily air temperature across all salinity treatments. We conclude that photosynthetic responses to seasonal changes in temperature and D, as well as seasonal temperature acclimation of leaf R, are largely consistent across a range of salinities in A. germinans . These results might simplify predictions of photosynthetic and respiratory responses to temperature in young mangroves.